Association between the mutational smoking signature and the immune microenvironment in lung adenocarcinoma. (September 2020) - Sato, Kei; Mimaki, Sachiyo; Yamashita, Riu; Togashi, Yosuke; Naito, Tomoyuki; Udagawa, Hibiki; Katsumata, Shinya; Nakasone, Shoko; Miyoshi, Tomohiro; Tane, Kenta; Aokage, Keiju; Sugano, Masato; et al.
Highlights: Not smoking history but smoking signature affects FOXP3 + T cell elevation. Smoking signature can be a biomarker for immune microenvironment. Smoking signature also associates with CD20 + B cell elevation. Abstract: Objectives: Mutational signatures associated with tobacco smoking (mutational smoking signatures: SS) are characterized mainly by C > A mutations. The aim of this study was to characterize the association between the tumor immune microenvironment and the SS in lung adenocarcinoma. Methods: Lung adenocarcinomas surgically resected from 96 patients, for which whole exome sequencing data was available, were included in the study. We extracted the SS from whole exome sequencing data, calculated the weights of SS using deconstructSigs, and compared the clinicopathological features of SS positive (SS+) and negative (SS-) adenocarcinomas. We selected 18 tumor pairs from SS + and SS- adenocarcinomas (sex, EGFR mutation, and tumor size-matched) and examined the expression of five immune markers (CD20, CD8, FOXP3, CD204, and PD-L1) by immunohistochemistry. Results: Of 96 specimens, there were 33 (34 %) SS + adenocarcinoma tumors. The smoking index significantly correlated with the weight of the SS (R = 0.43). Between SS + and SS- tumors, there was no significant difference in clinicopathological factors excluding smoking history. Immunohistochemistry revealed that the number of FOXP3 + T cells in SS + adenocarcinomas was significantly higher than that in the SS- adenocarcinomas (median number 58 vs. 36, p < 0.01). Also, the number of CD20 + B cells in SS + adenocarcinomas was significantly higher than that in the SS- adenocarcinomas (median number 77 vs. 29, p < 0.01); however; these phenomena could not be confirmed when stratified by smoking history. Conclusion: In lung adenocarcinoma, SS is associated with an immunosuppressive tumor microenvironment.